2007
DOI: 10.1086/511820
|View full text |Cite
|
Sign up to set email alerts
|

Photometry and Spectroscopy of 11 γ Doradus Stars

Abstract: We have used precise photometric and high-dispersion spectroscopic observations to study 11 Doradus stars, 10 of them newly confirmed. Only five of these 11 Doradus stars appear to be single; two are primaries of double-lined spectroscopic binaries, one is the secondary of a double-lined binary, two are primaries of visual binaries and, in the case of the double-lined binary (HD 86371), either or both components could be a pulsating Doradus star. We have determined a preliminary orbital period of 5.32 days for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 61 publications
(99 reference statements)
8
37
1
Order By: Relevance
“…Their periods range from 0.3 to 1.7 d, though two cases are known at longer periods, up to 2.7 d (Henry et al 2007(Henry et al , 2011. Our periods are compatible with this range.…”
Section: Group 4 Of Periodic Variables: γ Dor Candidatessupporting
confidence: 78%
“…Their periods range from 0.3 to 1.7 d, though two cases are known at longer periods, up to 2.7 d (Henry et al 2007(Henry et al , 2011. Our periods are compatible with this range.…”
Section: Group 4 Of Periodic Variables: γ Dor Candidatessupporting
confidence: 78%
“…Before the CoRoT and Kepler space missions sixty-six γ Dor variables were known, according to Henry et al (2007), and about 50% of them were found in binary stars (12 visual binaries, 10 double-lined, and 6 single-lined spectroscopic binaries, no EB). The first γ Dor in an eclipsing binary (VZ CVn) was announced by Ibanoǧlu et al (2007) but the quality and the coverage of their ground-based photometry was insufficient for a detailed asteroseismic study.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsation periods have previously been determined from photoelectric photometry for HD6568 (Henry et al 2011), HD17310 (Henry et al 2005), HD19684 (Henry & Fekel 2002), and HD62196 (Henry et al 2011). The ongoing analysis of our unpublished photometry of HD776, done in a manner similar to that outlined in the above papers, produces pulsation periods of 0.19968 and 0.19389 days.…”
Section: Pulsation Period Analysismentioning
confidence: 98%